2017
DOI: 10.1021/acs.jpcc.7b08509
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Photon Emission from Nonblinking Upconversion Nanoparticles

Abstract: Because of their well-known optical properties, upconversion nanoparticles (UCNPs) are regarded as some of the most promising nanomaterials for bioimaging, biosensors, and solar cells. The nonblinking nature of their upconversion emissions has been a particularly beneficial advantage for live-cell imaging. However, the origin of this unique property has never been seriously investigated. We report, for the first time, the observation of stochastic photon emission (SPEM) in core/shell UCNPs (NaYF 4 :Yb 3+ ,Er 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Furthermore, noticeable charge transfer and intermixing at oxide heterointerfaces result in the occurrence of a variety of point defects in conjunction with structural defects, which further convolutes the interface structure. Development of charge transfer ionic potentials for oxides, reactive force‐fields, bond‐valence interatomic potentials, and second‐nearest‐neighbor modified embedded‐atom method are prospective approaches that could address the complex charge transfer and related atomic‐scale processes at semi‐coherent oxide heterointerfaces, further assisting in comprehending the actual atomic and chemical structure of the interface. As recently demonstrated by Uberuaga and co‐workers, albeit for a heterointerface between metal and metal oxide, one promising strategy to investigate the structure of misfit dislocations at oxide heterostructures is to strain the film and the substrate so as to keep the supercell size tractable, while still incorporating the full misfit dislocation structure in the DFT supercell.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, noticeable charge transfer and intermixing at oxide heterointerfaces result in the occurrence of a variety of point defects in conjunction with structural defects, which further convolutes the interface structure. Development of charge transfer ionic potentials for oxides, reactive force‐fields, bond‐valence interatomic potentials, and second‐nearest‐neighbor modified embedded‐atom method are prospective approaches that could address the complex charge transfer and related atomic‐scale processes at semi‐coherent oxide heterointerfaces, further assisting in comprehending the actual atomic and chemical structure of the interface. As recently demonstrated by Uberuaga and co‐workers, albeit for a heterointerface between metal and metal oxide, one promising strategy to investigate the structure of misfit dislocations at oxide heterostructures is to strain the film and the substrate so as to keep the supercell size tractable, while still incorporating the full misfit dislocation structure in the DFT supercell.…”
Section: Discussionmentioning
confidence: 99%
“…For example, complete parameterization of the energy-level shown in Figure 1 based on experimental results will require further spectroscopic studies of all the photophysical processes involved and lead to a better model for UCNPs with improved theoretical understanding of the photophysics. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] For lanthanide-containing coordination complexes and clusters as well as smaller UCNPs, [47,48] the resulting faster diffusion will require new approaches, such as, for example, simulations incorporating ballistic dynamics combined with optical micro-spectroscopy experiments at higher frame rates. Furthermore, in such cases, the spectroscopic-stochastic dynamics may involve emitting quantum states in non-stationary populations, without clear timescale separation between photophysics and Brownian motion as shown here.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies have reported fundamental advances in our understanding of energy transfer mechanisms in UCNPs and core-shell UCNPs [20][21][22][23][24][25][26][27][28][29][30]. However, to the best of our knowledge, this work reports for the first time a comparison between experiments and simulations involving femtosecond and CW-induced upconversion with core-triple shell UCNPs containing with Gd III , Nd III , Yb III , and Er III ions.…”
Section: Introductionmentioning
confidence: 88%